2016
DOI: 10.4103/2230-8210.176349
|View full text |Cite
|
Sign up to set email alerts
|

Association between glycemic control and morning blood surge with vascular endothelial dysfunction in type 2 diabetes mellitus patients

Abstract: Objective:Morning blood pressure surge (MBPS) is an independent predictor of cardiovascular events. However, little is known about the association between glycemic control and MBPS, and its effect on vascular injury in patients with type 2 diabetes mellitus (T2DM). The current study examined the association between glycemic control and MBPS and the involvement of MBPS in the development of vascular dysfunction in T2DM patients.Materials and Methods:One hundred and twenty-two consecutive T2DM outpatients from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…One study shows that early detection of end‐organ damage like left ventricular hypertrophy is a cost‐effective method by nocturnal BP measurement using an HBPM device. In a study in 122 consecutive patients with diabetes, poor glycemic control and insulin resistance predicted the occurrence of morning BP surge . One more small study analyzed the role of genetic factors in BPV among the Kumba community, which showed significant differences in 24‐hour mean BP values, BPV, and nocturnal dipping in systolic BP.…”
Section: Blood Pressure Variability and Role Of Home Bp Monitoring (Hmentioning
confidence: 99%
“…One study shows that early detection of end‐organ damage like left ventricular hypertrophy is a cost‐effective method by nocturnal BP measurement using an HBPM device. In a study in 122 consecutive patients with diabetes, poor glycemic control and insulin resistance predicted the occurrence of morning BP surge . One more small study analyzed the role of genetic factors in BPV among the Kumba community, which showed significant differences in 24‐hour mean BP values, BPV, and nocturnal dipping in systolic BP.…”
Section: Blood Pressure Variability and Role Of Home Bp Monitoring (Hmentioning
confidence: 99%
“…However, there are few large‐scale studies on BPV and EMBS in the Indian population. One study in 122 consecutive patients with diabetes showed that poor glycemic control and insulin resistance predicted the occurrence of morning BP surge . Sultana et al studied the role of genetic factors in BPV among the Kumba community from the state of Chattisgarh, India .…”
Section: Evidence From Asiamentioning
confidence: 99%
“…Recent studies have shown that IR is a key factor for the occurrence and development of T2DM (Nuthalapati and Indukuri, 2016), and a major feature of T2DM (Zahra et al, 2013). As the target organ of insulin action, IR in the liver is a main component of the mechanism of T2DM (Polyzos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%